Empowering youth and women in Bangladesh through nursery entrepreneurship for sustainable rural development - Humaira, Bushra; Miajy, Abdullah; Haque, Abdul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
In rural Bangladesh, where most farmland is reserved for rice and cash crops, homestead gardening has become a way for families to get nutritious food and additional income. These small household plots, often managed by women, play a vital role in diversifying diets and strengthening food security, especially for land poor communities. Yet, year-round production has long been limited by one major challenge: access to quality seeds and seedlings. Locally developed nursery entrepreneurship is an excellent option for managing quality seeds/seedlings. With the support by the CGIAR Initiative for Sustainable Farming Systems, IRRI has trained seventeen young individuals, included two females and fifteen males, from Rangpur, Nilphamari, and Dinajpur districts through a nursery entrepreneurship training at the Horticulture Centre in Rangpur. The training covered commercial nursery design and management, selection of suitable vegetable and fruit varieties for seedling production, pest and disease management, and marketing strategies. Following the training, the participants established their own nurseries in their respective areas. Since then, they have grown and sold vegetable and fruit seedlings to neighboring farmers with support from IRRI and DAE. Local farmers are highly satisfied with the quality of seedlings and saplings provided by these nursery entrepreneurs, as the supply meets their demand effectively.